Social attention in anorexia nervosa and autism spectrum disorder: Role of social motivation. (October 2022) - Kerr-Gaffney, Jess; Jones, Emily; Mason, Luke; Hayward, Hannah; Murphy, Declan; Loth, Eva; Tchanturia, Kate
Research suggests a relationship between anorexia nervosa and autism spectrum disorder. The aim of the current study was to examine social attention in anorexia nervosa and autism spectrum disorder compared with age- and sex-matched typically developing groups, and to examine whether lowered social motivation could explain reductions in social attention across the two disorders. Participants' eye movements were tracked while watching a dynamic social scene. The proportion of fixation duration to faces, bodies and non-social areas of interest were compared across groups. Participants with autism spectrum disorder looked at faces significantly less often than controls, however, there were no differences between anorexia nervosa and controls in attention to faces. Typically developing -normed z -scores indicated that attention to faces showed the greatest deviation from normative data compared with body or non-social areas of interest in both autism spectrum disorder and anorexia nervosa, however, differences were larger in autism spectrum disorder than in anorexia nervosa. Social motivation scores did not predict attention to faces in either autism spectrum disorder or anorexia nervosa. Our results do not support the hypothesis that differences in social motivation underlie reduced social attention in both anorexia nervosa and autism spectrum disorder. Lay abstract: Research suggests a relationship between autism and anorexia nervosa. For example, rigid and inflexible behaviour, a preference for routine and social difficulties are seen in both conditions. In this study, we examined whether people with anorexia and people with autism show similarities in social attention (where they look while engaging in social interactions or watching a scene with people interacting). This could help us understand why people with anorexia and autism experience difficulties in social situations. Participants with either anorexia or autism, as well as participants with no mental health problems watched a video of a social scene while we recorded which parts of the scene they looked at with an eye-tracker. Participants also completed questionnaires to assess characteristics of autism. We found that autistic participants looked at faces less than typically developing participants. However, participants with anorexia did not show a similar reduction in attention to faces, contrary to our predictions. Autistic features were not related to attention in either group. The results suggest that autistic people may miss important social cues (like facial expressions), potentially contributing to social difficulties. However, this mechanism does not appear explain social difficulties in people with anorexia.